Persian medicine recommendations for the prevention of pandemics related to the respiratory system: A narrative literature review - Maryam Iranzadasl; Yasin Karimi; Fatemeh Moadeli; Mehdi Pasalar (Integrative Medicine Research)
Background: Pandemics of infectious diseases have long been regarded as societal challenges. This study aimed to summarize the theories of Persian medicine for controlling respiratory disease-related pandemics and to compare these theories with the findings of modern medicine. Methods: We searched the classic medical reference books of the 9th to 19th centuries for the terms ‘polluted air’ and ‘pandemic’, and we searched 4 databases (PubMed, Google Scholar, Science Direct, and Scopus) with the keywords ‘COVID-19’, ‘pandemic’, ‘history’, and ‘prevention programs’. The results were collected and subjected to content analysis. Results: From the point of view of traditional Iranian physicians, disease prevention is primarily possible by avoiding pathogenic factors. As a secondary solution, reducing one's susceptibility to the disease is crucial; this can be achieved through cleansing the body and strengthening the mood, reducing food intake, decreasing the internal humidity, disinfecting the house with herbal fumigation, and making use of pleasant aromas. Some of these recommendations are reaffirmed by modern research. Conclusion: Persian medicine techniques may be preventive during respiratory, influenza-like disease pandemics. However, rigorous studies are needed to confirm this hypothesis.